The role of Central and Eastern Europe in the building of silk road economic belt - Zuokui Liu (Međunarodni Problemi, 2015)
The author analyses how the unique market potential and geographic advantages of the Central and Eastern European countries (CEEC), the built and to be built projects, and diversified cooperation mechanisms between China and CEE laid the realistic foundation for the building of the Silk Road Economic Belt. China may have the following three choices to build the Silk Road Economic Belt: Model of "Development in Stages", Model of "Corridor Development" and Model of "Equal Development Between the East and the West". The three choices will have heavy influences on the functions and ways that the CEECs could play their roles. China faces with a series of challenges both domestic and international. In conclusion, the author suggests that the principle of tackling easy issues first and seeking gradual improvement should be pursued. While stepping up its strategic layout for a transportation corridor, Chinese Government should fully respect the law of the market, stress the leading role of enterprises and allow key projects to be the driving force, etc.